An empirical methodology for prediction of shape and flow rate of a free-falling non-submerged liquid and casting iron stream. (September 2016) - Gamez-Montero, PJ; Castilla, R; Freire, J; Khamashta, M; Codina, E
The work presented in this article demonstrates the use of an empirical and simplified approach based on an optical technique and a home-made ad hoc code that give knowledge of the shape and falling velocity of a free-falling non-submerged liquid stream to predict its typology and flow rate. The visualization photographic technique is a non-intrusive robust technique which can be applied to high-temperature liquids in harsh environments, such as an iron stream in a foundry. This technique allows predicting the liquid stream boundaries and contours without any type of treatment on the fluid. As a result of employing this empirical methodology, three flow typologies for a water stream are proposed and demonstrated experimentally. Comparisons with experimental data reveal satisfactory estimations of mean flow quantities. Finally, the approach used based on experimental visualization is carried out in an iron stream of a foundry, not being disruptive to in-situ foundry operations and showing its potential to improve performance of the cast parts' properties during the casting phase and revealing to be a useful tool for process optimization.